THE NEWCASTLE EXPERIENCE OF ANTI-MOG ASSOCIATED DISEASE. Issue 12 (15th November 2016) - Bolton, Clare; Chapman, James; Ledingham, David; Lewis-Smith, David; Spyropoulos, Achillefs; Guadagno, Joe; Duddy, Martin
Abstract : The original reports of anti-myelin oligodendrocyte glycoprotein (MOG) antibodies describe a predominant association with acute disseminated encephalomyelitis in children and with neuromyelitis optica spectrum disease (NMOSD) in adults. More recent studies broaden the spectrum of associated disorders to include recurrent optic neuritis and a picture similar to CLIPPERS (chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids). We performed a retrospective case note review of the presentation, imaging, laboratory findings and response to treatment of a group of 12 patients, aged 3–55 years, with CNS demyelinating disease, who tested positive (out of 117 tests) at a single centre. Our series shows a frequent biphasic pattern of illness. In over 75% there was an acute, often multifocal and highly steroid responsive first phase. In over half this was followed by a second phase, typically single or recurrent episodes of optic neuritis. Adult patients appear more likely to develop limited forms of the disease such as isolated recurrent optic neuritis or monophasic forms, though with significantly adverse outcomes in some cases. This pattern of disease following a suggestive initial presentation may have important implications for guiding both when to test for anti-MOG antibody and decisions on further therapy.